Evaluating sexual dysfunction and some related factors in women attending Sabzevar Health Care Centers - Z Bolourian; J Ganjloo (JRI, 2007)
Introduction: Women with perfect physical, emotional and mental health are bases of healthy families. The suppression of these divine needs will leave unfavorable effects on the cordiality and joys of couples. In assessing these needs, sex is not only a physiological need but also spiritual and gnostic as well. World Health Organization (WHO) contended that sexual health is the integrity and coordination of the mind, emotions and the body, and any disorder leading to dis-coordination and therefore dissatisfaction, can be associated with sexual dysfunction. Statistics have indicated that about 50% of couples may experience some forms of sexual disorders at some stages in their conjugal life but only a few are consulted and receive treatment. This research has been conducted to study sexual dysfunction and some related factors in women. Materials & Methods: This analytical-descriptive study was cross-sectionally conducted on 366 women referring to Sabzevar Health Care Centers in 2003. The sample population was selected through convenient non-probability methods. The data were collected by interviews consisting of demographic data, sexual patterns and an evaluation for sexual dysfunction. Data analysis was performed by SPSS software by using descriptive and non-parametric statistics such as Kruskal Wallis and Chi-squared with a confidences interval of 95%. Results: The findings indicated that 63.2% had experienced problems in their sexual relationships. Statistically significant correlations were observed between a history of conjugal life and sexual disorders where fewer disorders were reported for those with longer conjugal life (p=0.05). Higher sexual disorders were observed in women who had reported their libido low or high in comparison with the subjects with moderate sexual desire. Similar results were shown in the subjects’ spouses (p=0.001). Women dissatisfied with their coital relations, 3.90%, suffered from sexual dysfunction (p=0.003). A small number of women suffering from sexual dysfunction, 5.83%, had done nothing to solve their problems. Conclusion: One of the essential topics of premarriage counseling is to educate young couples to get a right understanding of their personal characteristics and tendencies, to direct their attitudes and beliefs and to train them to achieve correct skills and concepts of how to respond to their own physical and emotional needs. In fact, discovering and solving sexual problems by couples and getting a clear understanding of their concerns and helping themselves to build up and improve conjugal relationships, will have significant effects on increasing sexual satisfaction and will con-siderably prevent family disputes and problems.
Keywords: Sexual relations, Libido, Sexual satisfaction, Sexual dysfunction, Women, Mental health